Breeding Major Food Staples 2007
DOI: 10.1002/9780470376447.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Genetic Improvement

Abstract: PREFACEThis Handbook is the result of a combined effort by several current and previous cassava researchers at CIAT to review and summarize the most important results of cassava research during the past 40 years. Most of the chapters are based on the various presentations during the Regional Cassava Training Course, held in Thailand from October 6 to 17, 2008. This course was organized upon the realization that many people that were actively involved with cassava research in the 1970s and 80s, both at CIAT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 265 publications
(288 reference statements)
0
27
0
1
Order By: Relevance
“…The species originated in South America (Allem et al 2001;Olsen and Schaal 2001) and was domesticated less than 10,000 years ago. With the creation of the International Institute of Tropical Agriculture (IITA) in Nigeria and the International Center for Tropical Agriculture (CIAT) in Colombia in the early 1970s, a new era began for cassava with the implementation of successful breeding projects, modernization of cultural practices, and development of new processing methods (Cock 1985;Jennings and Iglesias 2002;Ceballos et al 2007). National research centers in Brazil, China, Colombia, Cuba, India, Nigeria, Thailand, Uganda, and Vietnam among many other countries have also conducted successful research on cassava.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species originated in South America (Allem et al 2001;Olsen and Schaal 2001) and was domesticated less than 10,000 years ago. With the creation of the International Institute of Tropical Agriculture (IITA) in Nigeria and the International Center for Tropical Agriculture (CIAT) in Colombia in the early 1970s, a new era began for cassava with the implementation of successful breeding projects, modernization of cultural practices, and development of new processing methods (Cock 1985;Jennings and Iglesias 2002;Ceballos et al 2007). National research centers in Brazil, China, Colombia, Cuba, India, Nigeria, Thailand, Uganda, and Vietnam among many other countries have also conducted successful research on cassava.…”
Section: Introductionmentioning
confidence: 99%
“…The main cassava-growing areas of the world were described by Ceballos et al (2007). Cassava is a perennial species grown as an annual crop.…”
Section: Introductionmentioning
confidence: 99%
“…That study also observed S 1 individuals with higher dry matter content and harvest index compared to S 0 . Desirable phenotypes have also been previously reported in S 1 cassava (Ceballos et al, 2004(Ceballos et al, , 2007. Inbreeding, therefore, presents opportunities to improve traits in cassava especially those that are quantitative in nature.…”
Section: Discussionmentioning
confidence: 85%
“…Cassava (Manihot esculenta Crantz) plays an important role in the tropics where it is the main source of calories and income for about 800 million of the world's poorest people. Even though the starchy roots of cassava are a valuable source of low-cost energy, their nutritional value is limited as they are poor in protein and essential micronutrients such as iron, zinc, or provitamin A (Ceballos et al 2007). The roots of nearly all commercial cassava cultivars and breeding populations are white, however natural genetic variation exists in the crop and some yellow-rooted cultivars and landraces have been identified that produce provitamin A carotenoids (Chávez et al 2005;Esuma et al 2012).…”
Section: Molecular Markers To Enhance the Breeding Efficiency For Higmentioning
confidence: 98%